2018
DOI: 10.1002/joa3.12064
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid minimally invasive technique with the bidirectional rotational Evolution® mechanical sheath for transvenous lead extraction: A collaboration between electrophysiologists and cardiac surgeons

Abstract: We report a case of a 63‐year‐old man referred for lead extraction with the bidirectional rotational Evolution® RL mechanical sheath because of systemic infection. As it was judged a “high‐risk” procedure, we opted for a “hybrid,” minimally invasive approach consisting in a minithoracotomic access. This technique is a feasible approach, and it might be a potential safer alternative in the most challenging transvenous lead extraction procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…One of the most recently developed mechanical techniques for TLE extraction is the mechanical sheath Evolution RL (Cook Medical) . The Evolution system comprises a powered sheath with a rotating tip that can cut through fibrous tissue, which significantly reduces the amount of traction and counter‐traction needed to extract the lead.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One of the most recently developed mechanical techniques for TLE extraction is the mechanical sheath Evolution RL (Cook Medical) . The Evolution system comprises a powered sheath with a rotating tip that can cut through fibrous tissue, which significantly reduces the amount of traction and counter‐traction needed to extract the lead.…”
Section: Discussionmentioning
confidence: 99%
“…The second‐generation Evolution device has been redesigned to address these problems; it has a bidirectional rotational mechanism, which prevents lead wrapping, and a less aggressive tip, which may reduce the risk of damage to coexisting leads and vascular structures. Initial single‐center experiences with a limited number of patients yielded promising results with the second generation of the Evolution mechanical extraction device . Recently, an Italian multicenter registry with a large study population demonstrated that the Evolution RL device is an effective TLE tool with high success rates with long‐implanted leads .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations